Hijabistas : An Analysis of the Mediation of Malay-Muslims and Modesty - Hassim, Nurzihan; Mat Nayan, Shahreen; Ahmad Ishak, Md Sidin (Jurnal Pengajian Media Malaysia, 2015)
“Hijab”, or the act of veiling among Muslim women, has been noted as an increasingly common practice in recent years in Muslim-majority countries such as Turkey, Indonesia or Malaysia. Scholars argue that its more modern, hybriditized identity is emergent in progressive, multicultural societies, particularly in these Muslim-majority countries (Saleh, 2010). In Malaysian media, the hijab and its association with a modest lifestyle is usually portrayed by Muslim women who are predominantly Malay. Years of socio-political developments in the nation state made Islamic cosmopolitanism an inevitable experience for Malay-Muslim women who are predisposed to the globalization of Islam and the ongoing negotiations by the Malay elite that seek to escape conservative Malay female stereotypes amidst Malaysia’s developing and multi-ethnic landscape. The current representations of the hijab offer a favourable status quo for Malay-Muslim women through marketing strategies that emphasize fashion trends and class mobility, thus disregarding the purpose of modesty in Islam altogether. This study administered a preliminary survey to explore attitudes and behaviours of female Malay-Muslim respondents towards the modern hijab in Malaysian media. In addition, interviews with media practitioners examined the construct of the modern hijab and its role in creating desire among the Malay-Muslim audience. The study found that the present phenomena is integrated with transnational flows of global media that commodified modesty to benefit marketers. The hijab is seen to have proliferated in today’s media enhancing the desire for Malay-Muslim media audiences to participate in the modern hijab movement and increase wider acceptance of the hijab.